Arthroscopic Technique for Chondrolabral Capsular Preservation During Labral Repair and Acetabular Osteoplasty - Benedict U. Nwachukwu, B.A.; Frank McCormick, M.D.; Scott D. Martin, M.D. (Arthroscopy Techniques, 2013)
Traditional techniques for acetabular osteoplasty in femoral acetabular impingement have required surgical detachment of the labrum at the chondrolabral junction. Such approaches compromise labral blood flow and contribute to a limited ability for healing at the chondrolabral junction. In this technical note and accompanying video, we present a technique for preservation of the chondrolabral junction during labral repair and acetabular osteoplasty. We elevate the chondrolabral complex subperiosteally off the acetabular rim, and the acetabular shelf is then contoured under fluoroscopic guidance. The labrum is then repaired and reconstituted to a new anatomic footprint. We find this technique to be advantageous because it preserves the blood flow to the labrum, thereby maximizing healing potential. Outcome studies are warranted to further elucidate the functional and outcome benefits of this surgical technique.